1991
DOI: 10.1007/bf00054746
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium and other ions in reperfusion injury

Abstract: Calcium-related mechanisms may play a role in several aspects of reperfusion injury. One proposal is that internal cytosolic calcium concentration is elevated early in the reperfusion period and that excess oscillations of calcium can very significantly contribute to reperfusion ventricular arrhythmias. Alternate hypotheses, such as those involving free radicals and the local tissue renin-angiotensin system, can be married to the existing hypothesis. Furthermore, the hypothesis allows for a role of the sodium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Maintained mitochondrial Ca 2+ homeostasis is suggested to improve ATP synthesis and maintain constant volume of the mitochondrial matrix [44]. These effects would preserve mitochondrial function of providing adequate ATP supply to cytosolic ATPase, which is essential to support the action of ATP-dependent ion pumps/exchangers and receptors, such as Na + /K + and Ca 2+ pumps [45], Na + /Ca 2+ exchangers and ryanodine receptors, to maintain cytosolic Ca 2+ homeostasis [19,46]. Thus limitation of [Ca 2+ ] m overload during I/R may represent a potential therapeutic target.…”
Section: Mitochondrial Integrity Is a Determinant Of Cytosolic Ca 2+ mentioning
confidence: 99%
“…Maintained mitochondrial Ca 2+ homeostasis is suggested to improve ATP synthesis and maintain constant volume of the mitochondrial matrix [44]. These effects would preserve mitochondrial function of providing adequate ATP supply to cytosolic ATPase, which is essential to support the action of ATP-dependent ion pumps/exchangers and receptors, such as Na + /K + and Ca 2+ pumps [45], Na + /Ca 2+ exchangers and ryanodine receptors, to maintain cytosolic Ca 2+ homeostasis [19,46]. Thus limitation of [Ca 2+ ] m overload during I/R may represent a potential therapeutic target.…”
Section: Mitochondrial Integrity Is a Determinant Of Cytosolic Ca 2+ mentioning
confidence: 99%
“…High-energy production is essential to support the action of ATP-dependent ion pumps, such as Na ϩ /K ϩ and Ca 2ϩ pumps, 21 to maintain membrane intactness and calcium ion gradients across various cell membranes, including the sarcolemma, sarcoplasmic reticulum, and mitochondria. 22 Xu and colleagues. 23 proposed that glycolytically derived ATP is functionally coupled to Ca 2ϩ transport by cardiac sarcoplasmic reticulum.…”
Section: Role Of the Diazoxide On Cardioprotectionmentioning
confidence: 99%
“…Nonetheless, it has been suggested that sometimes early restitution of blood flow after a period of hypoxia results in the deteriorous effects called reperfusion injury. 2,3) Intracellular Ca 2ϩ overload via activation of the Na ϩ /Ca 2ϩ exchanger after ischemic reperfusion has been indicated as a potential cause of this, which induces post-ischemic cardiac injury. 1,[3][4][5][6][7][8][9] Thus, inhibition of the Na ϩ /Ca 2ϩ exchanger, which would lead to prevention of Ca 2ϩ overload, could become a new approach for the treatment of ischemic reperfusion injury.…”
mentioning
confidence: 99%
“…As a peptidic inhibitor, Val-Met-Arg-Phe-NH 2 (1) with IC 50 value of 1.5 mM has been reported, which is a non-selective inhibitor. 10) As a non-peptidic inhibitor, aroylguanidine derivative (2) 11) with IC 50 value of 3.4 mM has been reported which is a modified amiloride derivative as is dimethylamiloride (3). 12) Furthermore, KB-R7943 (4), 13,14) SEA0400 (5), 15,16) benzyloxyphenyl derivative (6) 17) and SN-6 (7) 18) have been reported.…”
mentioning
confidence: 99%